2022
DOI: 10.1021/acsami.2c07145
|View full text |Cite
|
Sign up to set email alerts
|

Au@Cu2O Core–Shell and Au@Cu2Se Yolk–Shell Nanocrystals as Promising Photocatalysts in Photoelectrochemical Water Splitting and Photocatalytic Hydrogen Production

Abstract: In this work, we demonstrated the practical use of Au@Cu2O core–shell and Au@Cu2Se yolk–shell nanocrystals as photocatalysts in photoelectrochemical (PEC) water splitting and photocatalytic hydrogen (H2) production. The samples were prepared by conducting a sequential ion-exchange reaction on a Au@Cu2O core–shell nanocrystal template. Au@Cu2O and Au@Cu2Se displayed enhanced charge separation as the Au core and yolk can attract photoexcited electrons from the Cu2O and Cu2Se shells. The localized surface plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 68 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…The Cu 2p 3/2 peaks of MXene/Au/Cu 2 O shift to a lower energy region compared with Au/Cu 2 O and Cu 2 O, indicating that possible charge transfer from Au to Cu 2 O, and MXene to Au/Cu 2 O. 60 Fig. 3f presents the Ti 2p spectra of MXene and MXene/Au/Cu 2 O hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu 2p 3/2 peaks of MXene/Au/Cu 2 O shift to a lower energy region compared with Au/Cu 2 O and Cu 2 O, indicating that possible charge transfer from Au to Cu 2 O, and MXene to Au/Cu 2 O. 60 Fig. 3f presents the Ti 2p spectra of MXene and MXene/Au/Cu 2 O hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the performance, the structural modulation has been identified as another effective approach for Cu/Cu 2 O nanocomposite catalysts. By constructing the hollow nanostructure, the surface area and the reactive sites can be significantly increased, so that the inner cavity can be fully utilized and the photocatalytic performance can be enhanced. Yan et al prepared Cu/Cu 2 O hollow nanospheres for rapid photodegradation of methyl orange (MO) under visible light irradiation due to the porous nanocrystalline shell structure for solution penetration and unique heterojunction for carrier separation . Further research has demonstrated that the hollow structure can affect the solution diffusion for improving the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The CuO NPs exhibit excellent electrical, optical, magnetic phase, antioxidant and antimicrobial properties [ 2 , 3 , 20 ], which is useful in anti-cancer, biomedical imaging, drug and cellular deliveries, wound healing, and disease treatment, and they act as a heterogeneous catalysis [ 3 , 18 , 23 , 24 ]. In recent development, CuO NPs have great potential in various field of applications, which include advanced photocatalytic processes [ 25 ], environmental and energy conversion [ 26 ], green production of hydrogen, photoelectrochemical water splitting [ 27 ], organic pollutants’ photodegradation, generation of solar fuel and photovoltaic devices [ 28 ].…”
Section: Introductionmentioning
confidence: 99%